A hybrid system for voltage stability and placement optimization of STATCOM in distribution systems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A methodology is provided in this paper for determining the optimal assignment (i.e., sizingand position) of Distributed Generators (DGs) and static compensators (STATCOM) in aradial distribution system (RDS). The voltage stability index (VSI) is used to locate the bestSTATCOM position, and the fast voltage stability index (FVSI), and phase voltage stabilityindex (PVSI) are used to locate the best-distributed energy location. The suggested work ispresented as a non-linear optimal solution with a hybrid power stability optimization (HPSO),which is solved utilising a meta-heuristic/evolutionary-based approach in this paper. The Batmethod is used to determine the ideal dimensions of STATCOM in RDSs. Two basic IEEE34 and 85 bus RDSs are investigated in this study to assess the correctness, feasibility, andapplicability of the suggested optimal allocating method. In the RDSs, the experimentsdemonstrate a reduction in energy losses and an increase in bus voltages.